Application of remote sensing and GIS for hypsometric analysis of Bino watershed in Uttarakhand, India - MALIK, ANURAG (Journal of Soil and Water Conservation, 2021)
Remote sensing (RS) and geographical information system (GIS) have become powerful techniques for sustainable planning and management of water resources. This research utilizes RS and GIS for the hypsometric curve (HC) and hypsometric integral (HI) estimation of nine sub-watersheds (SWs) of a hilly watershed â€œBinoâ€, located in the upper Ramganga river basin in Uttarakhand State, India. The findings exposed three geological stages of the erosion cycle i.e., monadnock, mature and late youthful, and their HI ranges from 0.280 to 0.538 happened in the study SWs. The original soil mass in these subwatersheds is 28.0% to 53.8%. The results of this research could be useful for constructing suitable soil and water conservation structures at appropriate locations in the sub-watersheds of the Bino watershed.